Rancang Bangun Aplikasi Pengendalian Pembayaran Piutang Berbasis SMS Gateway Pada CV. Berkat Alam Sejahtera - Suharto, Octavianus; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
CV. Berkat Alam Sejahtera is a company engaged in the Gas Industry. CV. Berkat Alam Sejahtera sales in the process can be made by cash or credit. Customer confidence by making payments receivable directly to field officers can also pose a risk of abuse by field personnel. The administrative staff also often experience difficulties in the reporting process when managers need data of a customer sales and receivables suddenly because among the data is still not linked to one another. Based on the above, the company needs a sales application that can perform control of payments accounts of customers using SMS (Short Message Service) Gateway is also expected to address the delay in receivables collection customers with reminders customer receivables beginning of each month and increase customer confidence in making payments receivable with confirmation in the form of SMS so that customers feel safe and comfortable. Hopes that these applications can overcome the problems that had occurred, and increase sales and improve service to customers.